Peningkatan Kepatuhan Pajak Restoran Melalui Analisis System Thinking - Desty Deswita; Muslim Alkautsar; Dwirani Fauzi Lestari (Universitas Riau Kepulauan, 2026)
The culinary and tourism sector in Garut Regency has experienced significant development with the increasing number of restaurants, cafes, and tourist destinations that have the potential to boost regional revenue through restaurant and hotel taxes. Compliance of restaurant taxpayers is one of the key factors for increasing revenue for the region. This study aims to analyze the improvement of restaurant taxpayer compliance in Garut Regency. The research method uses descriptive qualitative methods and system thinking analysis. The object of this research is related to taxpayers' understanding, the implementation of digitalization, and restaurant tax compliance in Garut Regency. The research results show that taxpayers' understanding in Garut Regency is still limited to administrative aspects without being supported by an in-depth understanding of general tax regulations, the applicable tax system, and the role of taxes. The implementation of digitalization has provided convenience and efficiency but has not been optimally utilized and has not been able to encourage consistent compliance. Based on system thinking analysis, it indicates that the leverage points for improving compliance lie in strengthening educational socialization, increasing digital literacy, and optimizing the use of digital systems so that voluntary and sustainable compliance can be formed.